Emotional Vulnerability in Researchers Conducting Trauma-Triggering Research - Sarah Woods; Tina-Nadia Gopal Chambers; Ardavan Eizadirad (Ali Khorsandi Taskoh, 2022)
Qualitative researchers prioritize rapport-building to ensure safety of research participants and validity of data collected. Although there is extensive literature about prioritizing the safety and emotional well-being of research participants, much less has been written on the topic of researcher vulnerability with lack of consideration for researcher safety within ethics approval applications. The authors present a reflexive account of a research project involving interviews with young people aged 15 to 30 in Toronto, Canada who had firearm related charges. The methodological, ethical issues, and research burnout and vulnerability that arose due to the shared lived experience between the principal researcher and the research participants are discussed. Overall, the article explores the complexities and nuances involved when conducting research with topics that may be trauma-triggering and can contribute to researcher burnout and compassionate fatigue. It is argued that researchers are not immune to these risk factors and due to such exposure may experience depression and other negative side effects. Series of suggestions are outlined to reduce harm exposure for researchers and to improve how they can better be supported to cope and heal from conducting trauma-triggering research before, during, and after completion of a research project.